2012
DOI: 10.1002/btpr.1569
|View full text |Cite
|
Sign up to set email alerts
|

Decisional tool to assess current and future process robustness in an antibody purification facility

Abstract: Increases in cell culture titers in existing facilities have prompted efforts to identify strategies that alleviate purification bottlenecks while controlling costs. This article describes the application of a database-driven dynamic simulation tool to identify optimal purification sizing strategies and visualize their robustness to future titer increases. The tool harnessed the benefits of MySQL to capture the process, business, and risk features of multiple purification options and better manage the large da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…However, the ability of simulation software to accurately predict unit operation scale‐up and perform bioprocess optimization is limited (Shanklin et al, ). Still, several papers describe process economics for different mAbs (Farid, ; Stonier et al, ), although no data are available in the literature for viral vaccines with the exception of a very recent study of VLP process economics (Chuan et al, ). In this study, Monte Carlo simulation was employed to identify the variance in the unit production cost (UPC); through bioprocess simulation data it was shown that a vaccine could be manufactured at 1 cent (USD) per dose using bioreactor sizes of 300 and 500L.…”
Section: Process Understandingmentioning
confidence: 99%
“…However, the ability of simulation software to accurately predict unit operation scale‐up and perform bioprocess optimization is limited (Shanklin et al, ). Still, several papers describe process economics for different mAbs (Farid, ; Stonier et al, ), although no data are available in the literature for viral vaccines with the exception of a very recent study of VLP process economics (Chuan et al, ). In this study, Monte Carlo simulation was employed to identify the variance in the unit production cost (UPC); through bioprocess simulation data it was shown that a vaccine could be manufactured at 1 cent (USD) per dose using bioreactor sizes of 300 and 500L.…”
Section: Process Understandingmentioning
confidence: 99%
“…A database‐driven discrete‐event simulation tool for modeling the logistics and process economics of antibody processes was used as the core evaluation engine for this study. It was adapted to perform Monte Carlo simulations and handle the larger datasets required so as to mimic the impact of process fluctuations on the key outputs.…”
Section: Methodsmentioning
confidence: 99%
“…A database‐driven discrete‐event simulation tool was built to model the logistics and economics of alternative purification strategies. The overall structure along with the key input and output parameters is shown in Stonier et al The benefits of a database‐driven approach using MySQL (MySQL AB, Uppsala, Sweden) were exploited to capture the process, business, and risk features of multiple biopharmaceutical purification sequences in a multiproduct facility and better manage the large datasets required for multiple processes, uncertainty analysis, and optimization. The dynamic features of bioprocesses and impact of resource constraints, including suite availability, were captured through linkage to a discrete‐event simulation engine, Extend (Imagine That!…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations